Determining the Methods of Implementing the Individual Development Program of Music Teachers - Rasulova Maftuna Nasimboy qizi (Genius Journals, 2022)
This article analyzes the methods of designing the individual development program of music teachers, the problems encountered in the design, setting goals in the development project, and methodological aspects of its implementation
Keywords: Individual Professional Development; Individual Learning Trajectory; Motivation